2020
DOI: 10.1007/s00038-020-01494-0
|View full text |Cite
|
Sign up to set email alerts
|

Corona Immunitas: study protocol of a nationwide program of SARS-CoV-2 seroprevalence and seroepidemiologic studies in Switzerland

Abstract: Objectives Seroprevalence studies to assess the spread of SARS-CoV-2 infection in the general population and subgroups are key for evaluating mitigation and vaccination policies and for understanding the spread of the disease both on the national level and for comparison with the international community. Methods Corona Immunitas is a research program of coordinated, population-based, seroprevalence studies implemented by Swiss School of Public Health (SSPH+). Over 28,340 participants, randomly selected and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
117
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

10
0

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 17 publications
0
117
1
Order By: Relevance
“…The protocol for this longitudinal cohort study is reported elsewhere 4 . The study is part of a large nationally coordinated research network Corona Immunitas in Switzerland 5,6 . A random sample of schools, stratified by district, and randomly selected classes in lower school level (grades 1-2, attended by 6 to 9-year-old children), middle (grades 4-5, 9 to 13-year-old children), and upper school level (grades 7-8, 12 to 16-year-old children), ensuring that the same cohort of children within the class can be followed until April 2021.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for this longitudinal cohort study is reported elsewhere 4 . The study is part of a large nationally coordinated research network Corona Immunitas in Switzerland 5,6 . A random sample of schools, stratified by district, and randomly selected classes in lower school level (grades 1-2, attended by 6 to 9-year-old children), middle (grades 4-5, 9 to 13-year-old children), and upper school level (grades 7-8, 12 to 16-year-old children), ensuring that the same cohort of children within the class can be followed until April 2021.…”
Section: Methodsmentioning
confidence: 99%
“…We randomly selected classes within participating schools, stratified by school level: lower school level (grades 1 and 2; children aged 6-9 years); middle school level (grades 4 and 5; children aged 9-13 years); and upper school level (grades 7 and 8; children aged 12-16 years). We selected grades to ensure that the same cohorts would be in the classes until April 2021, when further testing is planned (children in grades 3, 6, and 9 often change class and school during the next [18][19][20][21][22]. We aimed to enrol at least three classes and at least 40 children from each school level at the invited schools.…”
Section: Populationmentioning
confidence: 99%
“…As of January 27, 2021, more than 100 million people were diagnosed with the coronavirus disease 2019 (COVID-19) and over 2 million died due to this infection (1). The majority of infected people are asymptomatic (2, 3) or have mild symptoms such as fever, cough, dyspnea, fatigue, or anosmia/dysgeusia (4, 5). However, severe COVID-19 symptoms can also be life-threatening and require to be hospitalized (6).…”
Section: Introductionmentioning
confidence: 99%